Institutional avenues for addressing climate, peace and security in Southern Africa - Synnestvedt, Thea; Mandlenkosi, Maphosa; Gadu, Siyaxola; Campbell, Raramai; Sax, Niklas; Maviza, Gracsious (2025)
Globally, Southern Africa is one of the regions most affected by climate impacts. While the region is relatively peaceful, it is evident that the impacts of climate on peace and security are manifesting in multifaceted ways. The region is seeing increased instability, conflict, and social tensions, largely attributed to the changes in the natural resource landscape. These include small-scale resource conflicts and the depletion of natural resource-based livelihoods, which worsen socio-economic conditions and inequality, thus amplifying vulnerabilities and exacerbating social tensions. Due to the major overlaps within the climate, peace and security nexus, there is a need to address these challenges intersectionally. However, current institutional set-ups are not necessarily designed to address such intersectional challenges. Therefore, the aim of the paper is to examine the existing institutional frameworks for climate change and identify potential entry points within the frameworks for climate, peace and security in Southern Africa, with particular focus on Madagascar, Malawi, Mozambique, South Africa, Zambia and Zimbabwe. To this end, this paper aims to: (1) understand the existing institutional frameworks for climate change; and to (2) identify opportunities for institutional incorporation of the climate, peace and security nexus within the national climate change response landscape.